INPP4B: the New Kid on the PI3K Block - Agoulnik, Irina U. (Impact Journals LLC, 2011)
Dysregulation of phosphatidyl inositol signaling occurs in many cancers and other disorders. The lipid and protein phosphatase, PTEN (Phosphatase and Tensin homology protein on chromosome 10), is a known tumor suppressor whose function is frequently lost in various malignancies due to mutations in the coding region or genomic deletions. Recently, another lipid phosphatase, Inositol Polyphosphate 4-phosphatase type II (INPP4B), has emerged as a potential tumor suppressor in prostate, breast, and ovarian cancers and possibly in leukemia. We will review its structure and function, crosstalk with androgen receptor signaling, and regulation of INPP4B expression, as well as existing data about its role in cancer.